2016
DOI: 10.3390/ijms17050648
|View full text |Cite
|
Sign up to set email alerts
|

Function of Lipid Storage Droplet 1 (Lsd1) in Wing Development of Drosophila melanogaster

Abstract: Perilipins are evolutionarily conserved from Drosophila to humans, the lipid storage droplet 1 (Lsd1) is a Drosophila homolog of human perilipin 1. The function of Lsd1 as a regulator of lipolysis in Drosophila has been demonstrated, as the Lsd1 mutant causes an increase of lipid droplet size. However, the functions of this gene during development are still under investigation. In order to determine the function of Lsd1 during development, Lsd1 was knocked down in Drosophila using the GAL4-UAS system. Selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In starvation conditions, acute TG lipolysis is induced in Drosophila , which is attenuated in the FB cells of AKHR mutant flies. Also, in vitro and in vivo studies have identified that Lsd-1 (PLIN1) is a PKA phosphorylation target that has a central role as a pro-lipolytic effector of the AKH/AKHR pathway on lipid droplet surface 73 . Our results show that Dome loss in the FB significantly reduced the effect of a HSD on AKHR and FASN expression, which may explain the decrease in TGs storage and a low expression of lsd-1 , despite the energy oversupply of a HSD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In starvation conditions, acute TG lipolysis is induced in Drosophila , which is attenuated in the FB cells of AKHR mutant flies. Also, in vitro and in vivo studies have identified that Lsd-1 (PLIN1) is a PKA phosphorylation target that has a central role as a pro-lipolytic effector of the AKH/AKHR pathway on lipid droplet surface 73 . Our results show that Dome loss in the FB significantly reduced the effect of a HSD on AKHR and FASN expression, which may explain the decrease in TGs storage and a low expression of lsd-1 , despite the energy oversupply of a HSD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Later in Drosophila development, wing imaginal discs accumulate surprisingly high levels of LDs that depend upon perilipin expression, which in turn is induced by a developmental transcription factor, vestigial ( Fauny et al, 2005 ). If perilipin is knocked down, mitochondrial-derived reactive oxygen species accumulate in the wing disc, many cells undergo apoptosis, and the wing remains small and misshapen ( Men et al, 2016 ). As a final example, Drosophila neuronal stem cells are maintained in a niche where the surrounding glia cells contain ample LDs to protect lipids from peroxidation reactions ( Bailey et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The wandering 3rd-instar larvae were dissected in PBS to collect wing imaginal discs. Approximately 20 to 30 wing imaginal discs were fixed in 4% formaldehyde in PBS and reacted with antibodies as described previously [67]. Anti-dLipin antibody [20], provided kindly by Prof. Dr. Michael Lehmann (University of Arkansas, Arkansas, USA), was used at a 1:3000 dilution, and then anti-rabbit IgG Alexa Fluor TM 594 (Molecular Probes, Invitrogen, Carlsbad, CA, USA) was used at a dilution of 1:800.…”
Section: Methodsmentioning
confidence: 99%